Warm Salt Water Immersion Therapy Can Reduce Scabies Pruritus - Tahratul Yovalwan; Asmawati Asmawati; Kheli Fitria Annuril (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
Scabies is one of the most common skin infections worldwide caused by infection of Sarcoptic scabiei var hominis that caused lesion and pruritus (itching). It is the most common skin disease in the community, especially at male students of the Islamic boarding school community. The purpose of this study was to identify the effect of warm salt water immersion therapy on reducing the pruritus of scabies among male students in Islamic boarding school. The research was a quasi-experiment with a pre-posttest design with a control group. The total of respondents was 56 male students with Scabies divided into two group, with 28 respondents each. The control group received warm water immersion. The intervention group received warmed sea salt water immersion on their legs, hands and toes with the duration of 10 minutes once a day for 6 days. The pruritus score data were collected using a pruritus severity scale questionnaire with 12 items. The t-test analysis showed that there is a different of mean pruritus scabies before and after intervention in both group scabies by 2.72. The warm salt water immersion therapy has a significant effect in reducing mean pruritus. The warm sea salt water soak therapy is more effective than warm water only (p-value; 0.000≤ 0.05). Warm sea salt water immersion therapy is easy to do for community and beneficial in reducing scabies pruritus and increase a sense of comfort and accelerate the healing of skin lesion.